Synthesis and Characterization of Ligand‐Linked Pt Nanoparticles: Tunable, Three‐Dimensional, Porous Networks for Catalytic Hydrogen Sensing. Issue 7 (12th July 2021) - Loof, Daniel; Thüringer, Oliver; Schowalter, Marco; Mahr, Christoph; Pranti, Anmona Shabnam; Lang, Walter; Rosenauer, Andreas; Zielasek, Volkmar; Kunz, Sebastian; Bäumer, Marcus
Abstract: Porous networks of Pt nanoparticles interlinked by bifunctional organic ligands have shown high potential as catalysts in micro‐machined hydrogen gas sensors. By varying the ligand among p‐phenylenediamine, benzidine, 4, 4''‐diamino‐p‐terphenyl, 1, 5‐diaminonaphthalene, and trans‐1, 4‐diaminocyclohexane, new variants of such networks were synthesized. Inter‐particle distances within the networks, determined via transmission electron microscopy tomography, varied from 0.8 to 1.4 nm in accordance with the nominal length of the respective ligand. While stable structures with intact and coordinatively bonded diamines were formed with all ligands, aromatic diamines showed superior thermal stability. The networks exhibited mesoporous structures depending on ligand and synthesis strategy and performed well as catalysts in hydrogen gas microsensors. They demonstrate the possibility of deliberately tuning micro‐ and mesoporosity and thereby transport properties and steric demands by choice of the right ligand also for other applications in heterogeneous catalysis. Abstract : Pt nanocatalyst construction kit : variants of stable Pt nanoparticle networks were synthesized from the same Pt nanoparticle building block and 5 different aromatic and aliphatic diamines as joints. These ligand‐linked networks demonstrate the possibility of deliberately tuning their microporosity for applications in heterogeneous catalysis by choice of the right ligand.